Osseointegration of dental implants in ectopic engineered bone in three different scaffold materials. Issue 1 (January 2020) - Naujokat, H.; Açil, Y.; Harder, S.; Lipp, M.; Böhrnsen, F.; Wiltfang, J.
Abstract: The in vivo regeneration of bone flaps might be an alternative to autogenous bone grafting. The first human case of mandibular reconstruction using the greater omentum as a bioreactor was reported in 2016. However, whether engineered bone will support the osseointegration of dental implants has not yet been investigated. In this study, bone tissue engineering was performed in the greater omentum of nine miniature pigs using bone morphogenetic protein 2, bone marrow aspirate, and three different scaffolds: hydroxyapatite, biphasic calcium phosphate (BCP), and titanium. After 8 weeks, two implants were placed in each scaffold; after another 8 weeks, the bone blocks were harvested for radiographic, histological, and histomorphometric analysis. All implants exhibited sufficient primary stability, and the success rate was 100%. The bone-to-implant contact ratios (BICs) were 38.2%, 68.5%, and 42.9%; the inter-thread bone densities were 29.4%, 64.9%, and 33.5%; and the peri-implant bone-scaffold densities were 56.4%, 87.6%, and 68.6% in the hydroxyapatite, BCP, and titanium groups, respectively. The BIC showed a strong correlation ( r  = 0.76) with the peri-implant bone-scaffold density. This study shows that de novo engineered bone leads to successful osseointegration and therefore may allow implant-based prosthodontic rehabilitation.